2023
DOI: 10.1029/2022jc019393
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Physical and Biological Controls on the Carbon Dynamics in a High‐Arctic Outlet Strait

Abstract: The many channels of the Canadian Arctic Archipelago (CAA) represent an important export pathway for Arctic outflow waters and the transport of freshwater to the North Atlantic (Carmack et al., 2016). Located between Ellesmere Island and Greenland, Nares Strait is the northernmost outflow gateway of the Arctic Ocean, and one of two main passages through the CAA (Figure 1). Nares Strait connects the Lincoln Sea, an ice-covered continental shelf sea, with northern Baffin Bay, which harbors the ecologically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 111 publications
(243 reference statements)
0
5
0
Order By: Relevance
“…An unstable Smith Sound ice arch allowed for increased export of sea ice from the Arctic Ocean into the NOW, was associated with a decline in marine primary production and little auk ( Alle alle ) colonies, and was coeval with an interval without evidence of human occupation in western Greenland (Ribeiro et al, 2021). Following Burgers et al (2023), it is possible that the positive phase of the Arctic Oscillation may have been associated with enhanced contributions of fresher and nutrient‐depleted waters from the Lincoln Sea into Nares Strait, exacerbating the unfavorable conditions for the biological productivity in the downstream NOW region. Jackson et al (2021) also inferred an increased northward inflow of Atlantic water and less efficient brine production, especially during the RWP but also during the Medieval Climate Anomaly (MCA; ca.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An unstable Smith Sound ice arch allowed for increased export of sea ice from the Arctic Ocean into the NOW, was associated with a decline in marine primary production and little auk ( Alle alle ) colonies, and was coeval with an interval without evidence of human occupation in western Greenland (Ribeiro et al, 2021). Following Burgers et al (2023), it is possible that the positive phase of the Arctic Oscillation may have been associated with enhanced contributions of fresher and nutrient‐depleted waters from the Lincoln Sea into Nares Strait, exacerbating the unfavorable conditions for the biological productivity in the downstream NOW region. Jackson et al (2021) also inferred an increased northward inflow of Atlantic water and less efficient brine production, especially during the RWP but also during the Medieval Climate Anomaly (MCA; ca.…”
Section: Discussionmentioning
confidence: 99%
“…This current upwells in the eastern sector of the NOW to the base of the turbulent surface layer, and a flow component also veers west to feed into the south‐flowing Baffin Island Current (Dumont et al, 2010; Melling et al, 2001). Colder and fresher (<−0.4°C; <33.5 psu; Münchow et al, 2015) silicate‐ and phosphate‐rich (up to 18 and 1.1 μmol kg −1 , respectively; Burgers et al, 2023) Pacific‐derived Arctic waters have been reported to enter the NOW from the north through Nares Strait (sill depth of 220 m; Lehmann et al, 2022; Tremblay et al, 2002) driven by strong and persistent northerly winds and a sea‐level difference between the Lincoln Sea and northern Baffin Bay. However, it is worth noting that the water mass assembly and nutrient content entering Nares Strait from the Lincoln Sea vary under different atmospheric forcing patterns (i.e., Arctic Oscillation modes), with increased contribution of the fresher and nutrient‐depleted (nitrate concentrations below 1 μM during winter; Brown et al, 2020) surface waters of the Canada basin during positive phases of the Arctic Oscillation and increased contribution of the comparatively nutrient‐rich waters (nitrate concentrations up to 3.5 μmol kg −1 ) of the Siberian shelves during neutral/negative phases of the Arctic Oscillation (Burgers et al, 2023).…”
Section: Ocean Circulation and Sea‐ice Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…To further elucidate the linkages between FDOM composition and microbial degradation (AOU), a water mass mixing approach was undertaken. The mixing fractions of predefined water masses using FDOM were previously estimated in the Indian Ocean (Kim et al., 2020), Nares Strait (Burgers et al., 2023), northwestern Pacific marginal seas (H. Han et al., 2023), northeast Atlantic Ocean (Álvarez‐Salgado et al., 2013), and the Arctic Ocean (Gómez‐Letona et al., 2022). Earlier studies in the Arctic Ocean have reported a positive linear relationship between humic‐like FDOM and AOU in the deep Baffin Bay/Labrador Sea waters (Gonçalve‐Araujo et al., 2016; Guéguen et al., 2014) and in the Atlantic halocline (AH) in the Canada Basin (DeFrancesco et al., 2023).…”
Section: Introductionmentioning
confidence: 99%